2018
DOI: 10.4103/ijri.ijri_113_17
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal malformations: Role of MRI in preoperative evaluation

Abstract: Purpose:To evaluate the spectrum of magnetic resonance imaging (MRI) findings in pediatric patients with anorectal malformation (ARM) and compare the accuracy of MRI and distal cologram (DC) findings using surgery as reference standard.Materials and Methods:Thirty pediatric patients of age less than 14 years (19 boys and 11 girls) with ARM underwent preoperative MRI. MRI images were evaluated for the level of rectal pouch in relation to the pelvic floor, fistula, and development of sphincter muscle complex (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This includes abdominal and pelvic ultrasound scans to evaluate associated urinary and reproductive tract malformations shortly after birth, cross table lateral radiograph to classify the malformation and a high pressure distal colostogram ( Figure 4 ) to define the specific type of rectourethral fistula in boys ( 1 , 25 , 83 , 84 ). Others include radiographs to prognosticate the condition and magnetic resonance imaging (and ultrasound scan) to define the anatomy, screen for tethered cord and evaluate for other associated malformations ( 25 , 83 86 ). While basic imaging is available in many centers, many patients will not benefit from some important evaluations because of absence of facilities, lack of radiologist, lack of fluoroscopy guidance or economic considerations ( 87 ).…”
Section: Surgical and Perioperative Considerationsmentioning
confidence: 99%
“…This includes abdominal and pelvic ultrasound scans to evaluate associated urinary and reproductive tract malformations shortly after birth, cross table lateral radiograph to classify the malformation and a high pressure distal colostogram ( Figure 4 ) to define the specific type of rectourethral fistula in boys ( 1 , 25 , 83 , 84 ). Others include radiographs to prognosticate the condition and magnetic resonance imaging (and ultrasound scan) to define the anatomy, screen for tethered cord and evaluate for other associated malformations ( 25 , 83 86 ). While basic imaging is available in many centers, many patients will not benefit from some important evaluations because of absence of facilities, lack of radiologist, lack of fluoroscopy guidance or economic considerations ( 87 ).…”
Section: Surgical and Perioperative Considerationsmentioning
confidence: 99%
“…However, ultrasound, CT, and MRI are helpful in differentiating presacral lesions. MRI is especially useful as it can assess all features of the Currarino triad accurately and help clarify additional pathologies, such as other malformations involving the uterus, vagina, anal sphincter, as well as those involving the spinal cord such as syringomyelia and intradural lipoma [ 7 - 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that MRI has advantages in revealing anomalies associated with ARMs, such as presacral masses; spinal, sacral and vertebral anomalies; and genitourinary malformations. Some previous studies have reported the diagnostic performance of MRI in fistula evaluation compared with other imaging modalities [7,11,[15][16][17]. However, in these comparative studies, colonography, voiding cystourethrogram, and fistulography were compared with MRI as one modality and were not differentiated.…”
Section: Discussionmentioning
confidence: 99%